2015
DOI: 10.1371/journal.pone.0131292
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Sialome of the Lone Star Tick, Amblyomma americanum, with a Glimpse on Its Time Dependent Gene Expression

Abstract: Hard ticks feed for several days or weeks on their hosts. Blood feeding is assisted by tick saliva, which is injected in the host skin regularly, alternating with blood ingestion. Tick saliva contains hundreds or thousands of different peptides and other bioactive compounds that assist feeding by inhibiting their hosts’ blood clotting, platelet aggregation, vasoconstriction, as well as pain and itching. Immunomodulatory and antimicrobial peptides are also found in tick saliva. Molecular characterization of tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 30 publications
10
124
0
2
Order By: Relevance
“…This was opposed to low levels, of between 3 -28%, observed in the secretory class of the sialotranscriptomes of Amblyomma ticks (Garcia et al, 2014;Karim and Ribeiro, 2015). The mouthparts of the ticks might offer one plausible explanation for the high levels of Glycine rich transcripts in the R. appendiculatus and R. pulchellus sialotranscriptomes, compared to the levels observed in Amblyomma ticks.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This was opposed to low levels, of between 3 -28%, observed in the secretory class of the sialotranscriptomes of Amblyomma ticks (Garcia et al, 2014;Karim and Ribeiro, 2015). The mouthparts of the ticks might offer one plausible explanation for the high levels of Glycine rich transcripts in the R. appendiculatus and R. pulchellus sialotranscriptomes, compared to the levels observed in Amblyomma ticks.…”
Section: Discussionmentioning
confidence: 69%
“…Seventeen percent of the predicted R. appendiculatus proteins were characterised as putative secretory proteins, which was in the same range as other tick sialotranscriptomes of about 13 -37% (Garcia et al, 2014;Karim and Ribeiro, 2015;Karim et al, 2011;Tan et al, 2015a).…”
Section: Discussionmentioning
confidence: 77%
“…The most represented protein families were Kunitz domain-containing proteins followed by Salp15/ixostatin family members, lipocalins, metalloproteases, and several novel protein family members of unknown function [56]. A very recent NGS study analyzed Amblyomma americanum salivary glands at four feeding time points and confirmed time-dependent preferential gene expression in another medically important tick [61]. The genetic mechanisms underpinning sequential expression of individual members of a multigene family are unknown.…”
Section: Gene Expression Dynamics During Tick Feedingmentioning
confidence: 99%
“…(A) Comparisons were made between various tick developmental stages [51,56] and as a function of tick blood feeding progress [50,64,56,60,61]. Differences in gene expression regulation were analyzed in the presence (infected ticks shown with green color in the figure) or absence of pathogens in ticks [78,70,71].…”
Section: Figurementioning
confidence: 99%
“…With the advent of next-generation sequencing (NGS) technologies, tick salivary gland transcriptomes have been described [23,[30][31][32][33][34][35][36][37][38][39]. However, the major limitation to these data is that it does not inform on which transcripts that encode for proteins are secreted in tick saliva.…”
Section: Introductionmentioning
confidence: 99%